2014
DOI: 10.1126/science.1246572
|View full text |Cite
|
Sign up to set email alerts
|

The HydG Enzyme Generates an Fe(CO) 2 (CN) Synthon in Assembly of the FeFe Hydrogenase H-Cluster

Abstract: Three iron-sulfur proteins–HydE, HydF, and HydG–play a key role in the synthesis of the [2Fe]H component of the catalytic H-cluster of FeFe hydrogenase. The radical S-adenosyl-l-methionine enzyme HydG lyses free tyrosine to produce p-cresol and the CO and CN− ligands of the [2Fe]H cluster. Here, we applied stopped-flow Fourier transform infrared and electron-nuclear double resonance spectroscopies to probe the formation of HydG-bound Fe-containing species bearing CO and CN− ligands with spectroscopic signature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
216
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(224 citation statements)
references
References 39 publications
5
216
2
1
Order By: Relevance
“…Likewise, CO synthesis by the WT enzyme will be impaired if the second cluster fifth iron is absent. This in turn could be provoked by incomplete cluster reconstitution, subsequent loss because of its inherent labile nature (19), or its removal as part of an Fe(CO) x (CN) y unit (23). Nevertheless, our results for CO production show that even with substoichiometric amounts of iron, there should be a variable fraction of HydG molecules that carry a functional second cluster (Fig.…”
Section: Significancementioning
confidence: 82%
See 1 more Smart Citation
“…Likewise, CO synthesis by the WT enzyme will be impaired if the second cluster fifth iron is absent. This in turn could be provoked by incomplete cluster reconstitution, subsequent loss because of its inherent labile nature (19), or its removal as part of an Fe(CO) x (CN) y unit (23). Nevertheless, our results for CO production show that even with substoichiometric amounts of iron, there should be a variable fraction of HydG molecules that carry a functional second cluster (Fig.…”
Section: Significancementioning
confidence: 82%
“…Indeed, site-directed mutational studies have shown that CO and CN − syntheses are affected by either the deletion of the maturase C-terminal region, where a second iron-sulfur cluster binds (22), or Cys-to-Ser mutations in its corresponding CxxCx 22 C binding motif (10,13). In addition, it has been shown that HydG synthesizes Fe(CO) x (CN) y precursors (x = 1 or 2; y = 1) of the [FeFe] catalytic unit (23). The two HydG crystal structures are very similar at the SAM and [4Fe-4S] cluster-containing (β/α) 8 TIM-like barrel, common to several radical SAM proteins (16) (Fig.…”
mentioning
confidence: 99%
“…The Fe-acyl bond constitutes the only stable acyl-organometallic compound found in nature, although an acyl-Ni species has been reported to be an intermediate in the acetyl-CoA formation reaction catalysed by acetyl-CoA synthase 8,9 . The metal cofactors of hydrogenases and their biosynthesis have been extensively explored to unravel their fascinating chemistry [10][11][12] and to use their H 2 activation capabilities for biotechnological applications 13,14 . In contrast to studies of [NiFe]-and [FeFe]-hydrogenases, convincing hypotheses and experimental data have not been reported for the biosynthesis of the Fe centre of [Fe]-hydrogenase, including the formation of the unique acyl-group, the greatest challenge in FeGP cofactor biosynthesis.…”
mentioning
confidence: 99%
“…Two alternatives have been considered [34] for assembly of the [2Fe] subcluster: (i) housekeeping enzymes also insert a [2Fe-2S] cluster which is modified by ligands introduced by transfer from HydG/HydE or (ii) the [2Fe] subcluster is derived from two equivalents of the Fe(CO) 2 CN synthon produced by HydG. Although many unresolved questions remain, using a biosynthetic cocktail (including maturases, substrates and cofactors) to achieve efficient transfer of labelled 57 Fe from HydG to the [2Fe] H subcluster of HydA [16] supports model (ii). Direct interactions between the maturase proteins HydE and HydG with HydF have been demonstrated [29,39] and GTP has been shown to accelerate the dissociation of HydE:HydF and HydG:HydF complexes [40], although the significance of these interactions and the GTPase activity awaits more detailed functional analysis.…”
Section: Hydf As a Scaffold For Hyda Maturationmentioning
confidence: 99%
“…Biochemical experiments with HydG identified three tyrosine derived products: the byproduct p-cresol [7], cyanide [13] and carbon monoxide [14]. The last two are incorporated into the [2Fe] H subcluster [15] together with HydG-derived iron atoms [16] The intermediate dehydroglycine is converted to CO and cyanide, a reaction that likely involves a second FeS cluster present in HydG, termed the auxiliary cluster [17]. The binding of these ligands to the auxiliary cluster was first reported using time resolved FTIR spectroscopy, which identified two further intermediates (Figure 1 c), complex A, formed after ~30 seconds, which is subsequently converted to complex B [12].…”
Section: Introductionmentioning
confidence: 99%